Built to change: dominance strategy changes with life stage in a primitively eusocial bee. (7th October 2020) - Orlova, Margarita; Treanore, Erin; Amsalem, Etya
Abstract: Access to reproduction is determined by an individual's dominance rank in many species and is achieved through aggression and/or dominance signaling. In eusocial insects, one or several dominant females (queens) monopolize reproduction but to what extent queens rely on aggression and signaling remains obscure. Aggression is costly and its efficiency depends on the group size, whereas signaling may reduce the risks and costs of aggression. Both strategies are used to regulate reproduction in social taxa, with aggression being more common in small social groups, compared to signaling in larger societies. Here, we examine the use of aggression and chemical signaling in a social species ( Bombus impatiens ) where the dominant queen interacts with increasing numbers of workers as she ages. We found that the queen's strategy to monopolize reproduction changes with life stage, shifting from overt aggression to chemical signaling as the queen gets older. Particularly, old queens exhibited a higher ratio of short to long cuticular hydrocarbons compared to young queens, an endogenous shift that was attributed to age, as all egg-laying queens were fecund and kept with the same number of workers. Our findings contribute to the understanding of reproductive dominance in the context of an individual's life history. Abstract : In different social environments, it takes different strategies to climb up the reproductive hierarchy and become dominant. Using bumble bees, we showed that the dominant female, who experiences a dramatic social change during her lifetime, changes strategies to keep up her dominance status as she ages. While young queens rely on aggression to inhibit worker reproduction, old queens use chemical signaling which they develop gradually with age.